2018
DOI: 10.1007/s40037-018-0433-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the literature on validity and assessment in medical education: a bibliometric study

Abstract: IntroductionAssessment in Medical Education fills many roles and is under constant scrutiny. Assessments must be of good quality, and supported by validity evidence. Given the high-stakes consequences of assessment, and the many audiences within medical education (e. g., training level, specialty-specific), we set out to document the breadth, scope, and characteristics of the literature reporting on validation of assessments within medical education.MethodSearches in Medline (Ovid), Web of Science, ERIC, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…The study was conducted in Canada which has been identified as a leader in research in HPE (e.g. : number of publications per medical school), in assessment and validity in medical education specifically, 15 and in medical education more broadly.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in Canada which has been identified as a leader in research in HPE (e.g. : number of publications per medical school), in assessment and validity in medical education specifically, 15 and in medical education more broadly.…”
Section: Methodsmentioning
confidence: 99%
“…Para que los resultados de los procesos de evaluación tengan un robusto sustento y se utilicen de forma apropiada, es indispensable abordarlos desde la lente de la validez. Validez de un proceso de evaluación es el grado con el que mide lo que se supone que mide, tradicionalmente se clasificaba como las tres C: de contenido, de criterio y de constructo (Buntis, Buntis y Eggert, 2017;Sánchez-Mendiola, 2015;Young et al, 2018). En las últimas décadas el concepto ha evolucionado a una definición más amplia (AERA, 2014;Gregory, 2016;Kane, 2016;Kane y Bridgeman, 2017;Shepard, 2016).…”
Section: Evolución Del Concepto De Validez Y Su Valor Como Lente De Análisisunclassified
“…For instance, Cook, Hatala, and Downing have helped bring argument‐based validity frameworks, such as those of Messick and Kane, 5,6 into the HPE assessment sphere 1–3,7–14 . St. Onge and Young have helped map out the current state of our field's understanding of validity 4,15–17 . Govaerts, Schuwirth, van der Vleuten, and others have progressed our fields view of validity in the context of programmatic assessment 18–26 .…”
Section: Introductionmentioning
confidence: 99%